2019
DOI: 10.1186/s13018-019-1124-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparative cost-effectiveness analysis of mechanical and pharmacological VTE prophylaxis after lower limb arthroplasty in Australia

Abstract: Background Venous thromboembolism (VTE) is a complication following surgery. Low-molecular-weight heparin (LMWH) or direct oral anticoagulants (DOACs) are efficacious but come with inherent bleeding risk. Mechanical prophylaxis, such as intermittent pneumatic compression (IPC), does not induce bleeding but may be difficult to implement beyond the immediate post-operative period. This study compared the cost and quality-adjusted life years (QALYs) saved of commonly used VTE prophylaxis regimens aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…We believe that the best and lowest cost-benefit for VTE prevention is related to the systematic use of intermittent pneumatic compression. This finding is in line with the opinion of other authors who consider that the association with the use of acetylsalicylic acid (ASA) increases its preventive power, 10 especially if used within the first 24 hours after surgery. ( 11 We found divergent opinions regarding the use of this protocol, as there is a fear that its application will not be enough to prevent DVT.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We believe that the best and lowest cost-benefit for VTE prevention is related to the systematic use of intermittent pneumatic compression. This finding is in line with the opinion of other authors who consider that the association with the use of acetylsalicylic acid (ASA) increases its preventive power, 10 especially if used within the first 24 hours after surgery. ( 11 We found divergent opinions regarding the use of this protocol, as there is a fear that its application will not be enough to prevent DVT.…”
Section: Discussionsupporting
confidence: 89%
“…In general, we found studies whose methods are similar to those adopted by Torres, Bautista and Lins, with incidences ranging from 0% to 3%. 10 )- ( 12 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the cost-effectiveness of different methods depended mostly on the cost of acquisition of the drug or mechanical prophylactic device and their complications 1280 . For instance, studies comparing rivaroxaban vs. LMWH in countries with more expensive rivaroxaban acquisition including Germany (from hospital perspective) and China, favored LMWH following either THA or TKA despite the higher efficacy of rivaroxaban in preventing VTE 1256 .…”
Section: - What Is the Cost-efficacy Of Each Vte Prophylactic Agent T...mentioning
confidence: 99%
“…They demonstrated IPCD with/without apixaban to be appropriate according to their cost-effectiveness profile. They recommended to use prophylactic measures in accordance with the bleeding/thrombosis risk of each patient 1280 .…”
Section: - What Is the Cost-efficacy Of Each Vte Prophylactic Agent T...mentioning
confidence: 99%
“…Our study also demonstrated high levels of unwarranted clinical variation in routine care to prevent infection and VTE after TKR and THR. The use of multiple prophylactic drugs, higher than recommended dose, and longer than recommended duration of prophylaxis, were surprising given the risks associated with inappropriate care [16,[47][48][49][50]. Prolonged VTE prophylaxis may increase the risk of bleeding; conversely when the duration or dose is insufficient, prophylaxis may be inadequate [50].…”
Section: Plos Onementioning
confidence: 99%